ChemInform Abstract: Dendrimers as Macromolecular Tools to Tackle from Colon to Brain Tumor Types: A Concise Overview. Issue 2 (14th January 2014) - Mignani, Serge; Majoral, Jean‐Pierre
Abstract Review: < 200 refs.